2022
DOI: 10.1002/pul2.12061
|View full text |Cite
|
Sign up to set email alerts
|

Critical role for the lung endothelial nonmuscle myosin light‐chain kinase isoform in the severity of inflammatory murine lung injury

Abstract: Global knockout of the nonmuscle isoform of myosin light-chain kinase (nmMLCK), a primary cellular regulator of cytoskeletal machinery, is strongly protective in preclinical murine models of inflammatory lung injury. The current study was designed to assess the specific contribution of endothelial cell (EC) nmMLCK to the severity of murine inflammatory lung injury produced by lipopolysaccharide (LPS) and mechanical ventilation ventilatorinduced lung injury or ventilation (VILI). Responses to combined LPS/VILI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…A key role of MLCK is to increase paracellular permeability, and numerous studies have shown that MLCK deletion, inhibition, or decreased activation decreases paracellular permeability in multiple cell types (37–41), with the most robust evidence in the vascular endothelium and the intestinal epithelium. Notably, MLCK mediates increased lung vascular endothelial permeability in LPS-induced lung injury (42–45). Further, mice have a marked increase in lung neutrophil infiltration after an i.p.…”
Section: Discussionmentioning
confidence: 99%
“…A key role of MLCK is to increase paracellular permeability, and numerous studies have shown that MLCK deletion, inhibition, or decreased activation decreases paracellular permeability in multiple cell types (37–41), with the most robust evidence in the vascular endothelium and the intestinal epithelium. Notably, MLCK mediates increased lung vascular endothelial permeability in LPS-induced lung injury (42–45). Further, mice have a marked increase in lung neutrophil infiltration after an i.p.…”
Section: Discussionmentioning
confidence: 99%
“…In ALI/ARDS in a clinical setting, the disruption of both the epithelial and vascular endothelial barriers occurs, resulting in the leakage of inflammatory cells and protein-rich effluent into the alveolar space [ 3 , 8 , 9 ]. Recent evidence suggests that MLCK-mediated regulation of the barrier function in vascular endothelial cells is important as per an ARDS model in MLCK-knockout mice [ 41 ]. In contrast, in a model of lung injury caused by pneumoedematogenic gas inhalation, MLCK inhibitors improved lung injury by enhancing the alveolar epithelial cell barrier function [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These EC actin-binding cytoskeletal effectors are involved in (a) regulation of vascular barrier processes, including inflammatory leukocyte trafficking (43,44); (b) vascular responses to ventilator-generated mechanical stress (45); and (c) harboring of genetic variants that are overrepresented in Blacks with ARDS and contributing to ARDS susceptibility and mortality (46,47). nmMLCK exhibits dual functionality as a proinflammatory effector contributing to lung EC reactive oxygen species (ROS) formation (48) and barrier disruption (49), but also a barrier-protective molecule in response to specific environmental cues. Both nmMLCK and cortactin are intimately involved in maintaining barrier integrity in quiescent ECs and are essential to the formation of a cortical actomyosin band at the cell periphery.…”
Section: Vascular Cytoskeletal Protein Involvement In Maladaptive Per...mentioning
confidence: 99%
“…Proinflammatory agonists, cytokines, DAMPs, PAMPS, and increased mechanical stress all significantly increase nmMLCK protein expression via hypoxia-inducible factors (HIF-1a/ HIF-2a) (58) with unique negative nmMYLK transcriptional regulation by nuclear factor erythroid 2-related factor 2 (NRF2)/antioxidant elements (59). These proinflammatory mediators robustly increase nmMLCK activity to elicit spatially localized central contraction, paracellular gap formation, and disruption of the lung vascular barrier in vitro and in vivo (45,49). The Ras homolog family member A (RhoA) guanosine triphosphatase (GTPase) directly binds and activates nmMLCK and is a significant promoter of EC permeability (60,61).…”
Section: Vascular Cytoskeletal Protein Involvement In Maladaptive Per...mentioning
confidence: 99%
See 1 more Smart Citation